EFFICIENCY OF A CONVEYOR DRYER - BABYN, IHOR; BURLAKA, SERHIY; KHOLODYUK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
On a large scale in Ukraine, a technical re-engineering is being carried out, technological installations of high single pressure are being introduced, which allow to reduce the total cost of capital investments, operating costs and product compatibility with a significant p movement of work productivity. Drying processes have become widely stagnant in all the galleys of the industry and the strong state, up to 15% of the entire vigorous fire is stained on them. Fruits, vegetables, dried brushes and other food products, which are colloidal-capillary-porous materials with water content of 35% to 95%, are not stable when harvested. The distance of water from them by way of drying up to a moisture content lower than 8-14% allows you to save their natural camp for a three-year period. Under the hour of drying, the product significantly changes, which reduces transport costs, costs for packaging and changes the need for warehouses. The article presents the results of experimental investigations, tabulation of indicators of the productivity of a conveyor dryer with other types of dryers. Such parameters were evaluated as the dryness of drying, the quality of the product, the amount of energy and the quality of operation. On the basis of the analysis of data, it was established that conveyor dryers may have few advantages over other types of dryers. The stench is safe for fast and equal drying of materials, reduces the cost of the product and ensures a decrease in energy consumption. In addition, stinks are designated by the old term of service and a changed service obligation. The results of the study confirm that conveyor dryers can be a viable choice for industries that require an efficient drying process. It is especially important to become the optimal option for large-scale tasks, where it is necessary to process large volumes of materials.